Population Knowledge and Attitude Toward Emergency Management of Avulsed Permanent Teeth - Gisele Lima Teles; Ellen Pereira Ribeiro; Joana Dourado Martins Cerqueira; Alessandra Castro Alves; Erica dos Santos Carvalho (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the knowledge of patients treated in a public University concerning dental avulsion and its emergency first-aid management. Material and Methods: Three hundred patients were invited to answer a questionnaire about demographic characteristics, attitude and knowledge of first-aid management of dental avulsion. Chi-square test was used to assess the association between knowledge about dental replantation and education level. Results: Female gender (66.7%) aged from 31 to 40 years (31.3%) with high school education (50.3%) predominated among all the participants. It was not found a difference between education level and management of avulsed permanent teeth (p=0.076), and 66% of the respondents were not able to do the replantation. In relation to the management of avulsed tooth, 42.7% of the respondents would brush the tooth and if the replantation was not possible, most of them would choose inappropriate media for storage. The association between the storage medium and educational level showed to be statistically significant (p=0.043). Conclusion: It was possible to notice the lack of knowledge about this subject, and it could result in the worst prognosis. In avulsion cases, the subsequent root resorptions may lead to the loss of the child's tooth. It is important to implement educational campaigns to spread knowledge and improve success rates of permanent avulsed teeth.